Implementasi Metode Pembiasaan untuk Meningkatkan Nilai Religius Santri di TPQ Al- Hikmah Bandung Kebumen - Khasanah, Nur; Fajriah, Siti Qoyimatul; Fatimah, Siti (IAINU Kebumen, 2024)
This study aims to determine the level of implementation of Islamic religious education materials with the habituation method to improve the religious character of students at TPQ Al-Hikmah Bandung. This research was carried out using the Classroom Action Research (CAR) method. The purpose of CAR is to improve and improve the quality of learning and to help empower teachers in solving learning problems in schools. The subjects of this study were students at TPQ Al-Hikmah Bandung. Data collection techniques were carried out using tests, non-tests, observations, interviews, documentation. The results showed that in cycle 1 students who completed reached 48%, and in cycle 2 students completeness reached 83%. It can be concluded that through Classroom Action Research there is an increase in the implementation of Islamic religious education materials